2021
DOI: 10.29040/jiei.v7i2.2615
|View full text |Cite
|
Sign up to set email alerts
|

Model Quadruple Helix Dalam Pengembangan UMKM (Studi Kasus Pada Industri Pisang Sale Kutacane Kab. Aceh Tenggara)

Abstract: This study aims to obtain a comprehensive picture of the synergy of banana sale stakeholders in Kab. Southeast Aceh. The Quadruple Helix model is one suitable model for social research and innovation. This study uses a qualitative research design with a phenomenological approach that seeks to understand the perspectives, thoughts and experiences of stakeholders regarding the synergy of Quadruple Helix stakeholders in realizing the development of the banana sale business in Kab. Southeast Aceh. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Meanwhile, Mulyana and Sutapa (2014) linked the Quadruple Helix model (Intellectual, Government, Business, Civil Society) with creativity. Furthermore, Yolanda (2021) found discrepancies in vision and mission among policy stakeholders and coordination issues among MSMEs in the banana fritters industry, leading to various challenges in business development. Another related study by (Latisia, 2017) revealed suboptimal performance in the empowerment strategy of the Cooperatives and MSMEs Office in empowering micro, small, and medium enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Mulyana and Sutapa (2014) linked the Quadruple Helix model (Intellectual, Government, Business, Civil Society) with creativity. Furthermore, Yolanda (2021) found discrepancies in vision and mission among policy stakeholders and coordination issues among MSMEs in the banana fritters industry, leading to various challenges in business development. Another related study by (Latisia, 2017) revealed suboptimal performance in the empowerment strategy of the Cooperatives and MSMEs Office in empowering micro, small, and medium enterprises.…”
Section: Introductionmentioning
confidence: 99%